The complete chloroplast genome of Nicotiana plumbaginifolia. Issue 1 (2nd January 2022) - Tong, Zhijun; Du, Tianyu; Hu, Yiyu; Chen, Haijun; Shen, Enhui; Fan, Longjiang; Xiao, Bingguang
Abstract: Nicotiana plumbaginifolia Vivianiis 1802 is an annual herb, native to Mexico and South America. It is one of the most widely distributed tobacco species. As a wild tobacco, N. plumbaginifolia has provided several economically important disease-resistance genes to cultivated tobacco. We assembled the complete chloroplast genome of N. plumbaginifolia . The chloroplast genome is 155, 945 bp in length, which includes a large single copy region (86, 621 bp), a small single copy region (18, 528 bp) and two separated inverted repeat regions (25, 398 bp). A total of 117 unique genes were annotated, consisting of 84 protein-coding genes, 29 tRNA genes and 4 rRNA genes. Based on chloroplast genomes of 17 Nicotiana species, phylogenetic analyses indicated that N. plumbaginifolia was closely related to N. suaveolens and N. amplexicaulis .